Governance Theory als fortentwickelte Steuerungstheorie? - Renate Mayntz (Max Planck Institute for the Study of Societies, 2004)
Gegenstand dieses Papiers ist die Entwicklung des mit dem Leitbegriff Governance verbundenen analytischen Ansatzes und sein Zusammenhang mit dem steuerungstheoretischen Paradigma. Governance ist, so wird argumentiert, keine einfache Weiterentwicklung von Steuerung, sondern lenkt die Aufmerksamkeit auf andere Aspekte der politischen Wirklichkeit. Während die Steuerungstheorie einem akteurzentrierten Ansatz folgt, ist die sich entwickelnde Governance-Theorie institutionalistisch und fragt nach der Beschaffenheit von Regelungsstrukturen, in denen öffentliche und private, hierarchische und netzwerkartige Formen der Regelung zusammenwirken. – – In this paper the development of the paradigm of political steering (Steuerungstheorie) and how it intersected with the development of the concept of governance is analyzed. It is argued that use of the term governance does not indicate a simple extension of the analytical frame underlying the theory of political steering. The concepts politische Steuerung and governance refer to different aspects of political reality. Politische Steuerung is the hallmark of an actor centered approach to policy-making, while 'governance is the hallmark of an institutionalist approach dealing with regulatory structures combining public and private, hierarchical and network forms of action coordination.
Keywords: 300